Potensi Nomophobia dan Model Mental Anak dalam Menghafal Al-Qur’an - Subhan, Subhan; Rahmah, Nur (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2017)
This study reveals the link between the potential of nomophobia and the mental model of the child formed when memorizing al-qur'an. Basically, nomophobia is interpreted as a communication pathology in the form of a psychological disorder that causes children to feel restless and uncomfortable when away or can not access their gadgets instantly. Nevertheless, the research findings indicate a positive trend between nomophobia as a psychological disorder with a mental model that plays a vital role in determining students' ability to memorize al-qur'an. This is reflected in the activity of memorizing al-qur'an especially in conditioning sessions using video, images and religious ceremony before starting memorizing al-qur'an.Anak who have the potential or tendency nomophobia have a better mental model in memorizing al-qur ' an. This is due to the breadth of virtual experience that children get from using gadgets that can form their positive mental models when memorizing the Qur'an. This further affects the formation of strong emotions, the motivation to maintain memorization, foster awareness and better understanding of morals. Teachers and parents should create some conditions of use of gadgets based on the intensity of usage time, content accessed by children, and positive control over the child's negative behavior that arises.